Condylar Displacement on Closure as a Risk Indicator for Internal Derangement of the Temporomandibular Joint. - Chang, Steve. (2017)
Abstract: Aim: The objective of this study was to determine whether direction and magnitude of condylar displacement on closure may be risk indicators for internal derangements of the temporomandibular joint. Introduction: Occlusion's role in internal derangements of the temporomandibular joint (TMJ) disorders is still a highly debated topic in dentistry despite the anatomical association between the dentition and condylar position. The role of joint loading beyond the adaptive capacity of the temporomandibular joint complex and the pathogenesis of temporomandibular joint disorders is beginning to gain traction in the literature. The terminal stop of the joint and invariably the stresses placed on the joint are determined by the dentition at maximum intercuspation. Therefore the association between dental occlusion and temporomandibular joint disorders may just be the role of the dentition in preventing excessive load on the temporomandibular joint. Disharmony between the arc of closure of the mandible and the final seated position of the dentition may signify an incongruence of the condylar position which may have deleterious effects on the TMJ and its disc. Methods: Eighty three patients (166 temporomandibular joints) were given a diagnosis for the presence or absence of internal derangement of each temporomandibular joint using the Research Diagnostic Criteria for Temporomandibular Disorders (RCD/TMD). Two mandibular positions were registered for each patient, maximum intercuspal position (MIP) and a neuromuscularly deprogrammed/occlusal first contact position. Using a Panadent® CPI - III Condylar Position Indicator the condylar displacement between MIP and the first contact position was determined in three dimensions. Generalized estimating equations (GEE) were used in the analysis. Results: The association between the superior direction of condylar displacement and the internal derangement of the TMJ was positive and statistically significant (p=0.0425). This association remained positive and significant when adjusting for magnitude (p=0.0499). However, no significant association was found between the magnitude of condylar displacement in the superior-inferior plane and internal derangement of the TMJ (p=0.7803). When adjusting for superior-inferior direction there remained no significant association (p=0.7471). A positive and statistically significant association was found between the magnitude of condylar displacement in the medial-lateral dimension and internal derangement of the TMJ, adjusting for medial-lateral direction (p=0.0285). However, condylar displacement in the medial-lateral direction showed no significant association when assessing only the magnitude (p=0.0564) of displacement. Similarly, when assessing only the direction of displacement, no association was found (p=1.0000). Furthermore, when adjusting for magnitude, the direction of displacement in the medial-lateral direction remained insignificant (p=1.0000). All other associations were not statistically significant (p>0.05) Conclusion: Superior condylar displacement may be associated with internal derangement of the temporomandibular joint. The magnitude of condylar displacement in the medial-lateral direction may also be associated with internal derangement of the temporomandibular joint. No significant associations were found between internal derangement and the direction and magnitude of condylar displacement in the anterior-posterior direction. The association found in this study between condylar displacement and internal derangement of the temporomandibular joint, albeit inconsistently, may be indication of an orthopedically unstable occlusion leading to an orthopedically unstable condylar position. This orthopedically unstable joint complex may increase the risk for internal derangement of the temporomandibular joint. Therefore, measuring condylar displacement may represent a new dogma on measuring occlusion and its effects at the condylar level which may give further insight on the effect of condylar position on TMD.; Thesis (M.S.)--Tufts University, 2014.; Submitted to the Dept. of Other.; Advisors: George Maloney, and Noshir Mehta.; Committee: George Maloney, Noshir Mehta, Matt Finkelman, and Ronald Kulich.; Keyword: Dentistry.